Combined fuel cell?gas turbine plant for highly efficient power generation from renewable energy sources. (7th August 2007) - Monsberger, Michael; Hacker, Viktor; Fraser, Simon; Sanz, Wolfgang; Luckel, Florian; Jericha, Herbert
The impact of renewable energy sources on today's energy supply substantiates the importance of hydrogen as an energy carrier. Hydrogen can be directly produced from solar energy and is considered a promising technology for temporary storage of electrical energy from wind turbines and photovoltaic systems. The generation of electrical energy from stored hydrogen requires highly efficient systems such as the so-called H2-Graz-Cycle, which is discussed in this paper. The H2-Graz-Cycle is a closed steam process based on the stoichiometric combustion of oxygen and hydrogen. It is shown that efficiencies of up to 51% can be achieved with the H2-Graz-Cycle even with small output powers in the range of 1.35 MWel. The process is thus particularly suitable for decentralised applications. It is further shown that the cycle efficiency can be significantly increased to a level of 75% by integrating a high temperature fuel cell into the cycle.